Prevalence of asymptomatic femoroacetabular impingement in Turkey; cross sectional study - Polat, Gökhan (Acta Orthop Traumatol Turc, 2018)
OBJECTIVES: Femoroacetabular impingement (FAI) is one of the causes of hip pain in young-adult patients. The purpose of our study is to determine the prevalence of radiological FAI findings in asymptomatic population in Turkey. METHODS: Trauma patients aged 18–65 years who applied to the emergency service between September 2015 and September 2016 were retrospectively evaluated for this study. After a preliminary study and power analysis, 2152 hips of the 1076 previously asymptomatic patients were evaluated radiologically with pelvis antero-posterior and frog-leg radiographs. On radiographs of these patients; alpha angle, lateral central edge angle (LCEA), Tönnis angle (TA) and collodiaphyseal angle were measured. Alpha angle values higher than 55° were noted as cam type FAI. TA values lower than 0° or LCEA values higher than 39° were noted as pincer type FAI. LCEA values lower than 25° or TA values higher than 10° were noted as acetabular dysplasia. RESULTS: Mean age of 1076 patients (602 female, 474 male) was 42.1 ± 15.6 years. The assessment showed that 15.9% of the patients had cam type, 10.6% had pincer type, 3.1% had combined type FAI and 9.3% had findings of acetabular dysplasia. The prevalence of asymptomatic FAI is significantly more in males (46%) in comparison to females (17%) in Turkey. CONCLUSION: Even though FAI is considered to be a pathology associated with hip osteoarthritis; it is very common in asymptomatic population. In this respect, our study showed that prevalence of radiological FAI findings in asymptomatic adult population was 29.6% in Turkey.